Stability of civil works in the crown of Costanera Malecón, San Miguel District - Lima - Gallarday Bocanegra, Tomás (2017)
This study indicates the causes that determined the prematural deterioration of the civil work, located on the waterfront of the Malecón La Costanera section Av. Universidad Av. Rafael Escardo San Miguel LIMA, confirms the work did not meet its useful period guaranteed by the Constructor consortium , part of it was made on an uncontrolled landfill, verified with pits, geological mapping and the erosion caused by the marine dynamics, add the calculations made by using the numerical results of the tests and analyzes carried out in the UNI. Application of the Terzaghi formula and the Monobe Okabe method. Support of the recommendations given in the responsibilities matrix.The work in 80% was built on a surface obtained on uncontrolled landfill (dump, formed by solid waste from civil works made in the Lima megalopolis), the difference is on a surface of a natural soil, formed by silts, sands, gravels , pebbles and peat of irregular sequence given by layer on layer with little cementing material (clays), process occurred in hundreds of years, has good packaging. Load resistance> 3 kg / cm2.The layers of soil in fan is the result of different cumulative stages given in the dump from the expansion, modernization and urban vertical growth of Lima. Decade 1980 - 203 (constructive boon). This soil has low packing, carrying capacity qa = 1.7 kgs / cm2. [Terzaghi] Indicator that will rise if it is dosed with clayey soil, affirmed, cultivation soil, or grout oxide of cement or lime is injected, which will give optimum compression behavior (roller), thus stabilize the uncontrolled filling, the cementing material will be in a ratio of 2 / 10m3, process that will form a floor folder with loan material, which will be 2m thick in the five failed sectors [fault plane], the use of excess water in the crown of the embankment slope accelerates the local circular faults.To be installed on the stable or stepped stable slope 62% = 28º, xerophilous vegetation, crossula sp, cacti, grasses variety ray grass poaceae, schinus molle, shrubs and trees, the civil works will fulfill their useful period. It is indicated that the edge of the beach in this sector requires protection by constructing two groynes or perimetric collar based on silicified andesite rocks.